2008
DOI: 10.1002/ptr.2302
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and hypolipidemic effects of Costus speciosus in alloxan induced diabetic rats

Abstract: Hyperglycemia, abnormal lipid and antioxidant profiles are the most usual complications in diabetes mellitus. In the present study, the antihyperglycemic, antihyperlipemic and antioxidant potency of an ethanol extract of Costus speciosus root was investigated in alloxan-induced diabetic male (Charles Foster) rats. Four groups of alloxan diabetic rats (n = 6) were administered orally with different doses of Costus speciosus root extract (150, 300 and 450 mg/kg BW) and a standard drug, glibenclamide (600 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…In the present study, some of the diabetic non-treated control animals all died on day 10 post-induction of diabetes whereas the extract-treated group survived beyond the period of the experiment. Effective control of blood glucose level is a key step in preventing and reversing diabetic complications, and improving the quality of life of diabetic patients (Bavarva and Narasimhacharya, 2008). Hence, chronic administration of the extract may cause a progressively sustained reduction in hyperglycaemia known to reduce the risk of complications associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, some of the diabetic non-treated control animals all died on day 10 post-induction of diabetes whereas the extract-treated group survived beyond the period of the experiment. Effective control of blood glucose level is a key step in preventing and reversing diabetic complications, and improving the quality of life of diabetic patients (Bavarva and Narasimhacharya, 2008). Hence, chronic administration of the extract may cause a progressively sustained reduction in hyperglycaemia known to reduce the risk of complications associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
“…So, pretreatment of animals with SC and/or Liv-52 reduces significantly the levels of these parameters suggesting their hepatoprotective potential [51]. According to Bavarva and Narasimhacharya [52], Costus speciosus root extract possesses anti-hyperglycemic, antihyperlipidemic and antioxidative effects, which may prove to be of clinical importance in the management of diabetes and its complications. It was reported that, the ethanolic extract of Costus species showed significant reduction in glucose, urea, total cholesterol in blood of Albino rats [53].…”
Section: Discussionmentioning
confidence: 97%
“…Ten percent neutral buffered formalin was used for saving liver specimens. The specimens were embedded in paraffin to prepare for sectioning (4)(5) …”
Section: Histopathological Studymentioning
confidence: 99%
“…Its extract is also used to control syphilis in Japanese traditional medicine (Jain, 1991). C. speciosus possessed various activities: antibacterial, antifungal (Ibrahim et al 2017), anti-inflammatory, analgesic, antihyperglycemic, antihyperlipidemic, antipyretic, and antioxidant (Bavarva and Narasimhacharya, 2008;Srivastava et al, 2013). Moreover, C. speciosus saponins had antifertility and oestrogenic activities (Tewari et al, 1973).…”
Section: Introductionmentioning
confidence: 99%